Effects of supervisors’ leadership styles on job satisfaction in the logistics industry - Tsepetsi, Tshepo Kingsley (Vaal University of Technology, 2017)
The purpose of this study is to investigate the effects of supervisors‟ leadership styles (transformational, transactional and passive-avoidance) on job satisfaction in the logistics industry. This study advocates the way in which employees perceive their supervisors‟ leadership styles and their influence on job satisfaction. The fact is that employees play an indispensable role in the realisation of an organisation’s goals and therefore it would be more crucial for an organisation to have employees who are willing to go beyond what is required of them. In this study, a quantitative research method was used to investigate a sample size of 201 employees working in logistics departments in organisations situated in Southern Gauteng. In choosing a sampling method, convenience sampling method was used mainly because respondents were readily accessible and available to the researcher and also willing to participate in the study. Data were collected with the aid of a structured questionnaire and the results of the correlation analysis revealed that transformational, transactional, and passive-avoidance leadership styles are significantly and positively related to job satisfaction. Based on the findings of the empirical survey, it was revealed that a positive association was found between transformational leadership and job satisfaction. A negative correlation was found between transactional, passive-avoidance and job satisfaction. Furthermore, the regression analysis showed that a transformational leadership style positively influences job satisfaction. Therefore, it was recommended that, to address negative correlations between transactional leadership styles on job satisfaction, supervisors/managers elicit desired performance from subordinates by motivating them externally. This can be done by rewarding subordinates for behaving in the expected manner and punishing them if they deviate. It was also recommended that to address negative correlation between passive-avoidance leadership style and job satisfaction supervisors/managers ought to give subordinates autonomy to make their own decisions and be able to solve work-related problems independently. It is further recommended that since passive-avoidance leadership style is associated with unproductiveness, supervisors/managers avoid the use of such a leadership style. The study concludes by recommending that a newer style of leadership such as authentic leadership can be introduced in order to influence employee job satisfaction positively. Servant leadership style can also be applied as this may influence job satisfaction positively. The findings and recommendations of this study are important for supervisors/managers employed in the logistics industry since they provide insight regarding the styles of leadership that are more effective in influencing employee job satisfaction positively. The implications for future research offer several opportunities in the area of leadership and job satisfaction. The study used a quantitative research design whereas the use of a mixed method approach may provide more meaningful results. Since the sample size was restricted, the study could also be expanded to include employees from other departments, such as finances, human resource and marketing.
M. Tech. (Department of Human Resources Management, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Supervisors; Leadership styles; Job satisfaction; Effects; Logistics; Industry; Dissertations, Academic -- South Africa.; Business logistics -- Management.; Job satisfaction.; Supervisors -- Employee rating of.